Collective Action for Public Health, Fragmented Action for Public Peace: Institutional Resilience and Failure in Ethiopia's Religious Councils - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2026)
Ethiopia’s Inter‑Religious Council of Ethiopia (IRCE) successfully mobilised collective action against COVID‑19 but has failed to mediate the country’s multiple ethnic conflicts. This paradox challenges assumptions about the peacebuilding potential of religious institutions. This study investigates why the same religious institutions demonstrate high collective action for public health but fragmentation for peace, testing whether threat type (exogenous vs. endogenous) explains divergent outcomes. A comparative case study design was employed, comparing the IRCE’s response to COVID‑19 (exogenous threat) with four ethnic conflicts (endogenous threats): Tigray, Oromo, Amhara, and Gurage. Data sources included IRCE public statements, news archives, ACLED conflict data, NGO reports, and peer‑reviewed literature. Analysis traced five criteria: public statements, ceasefire calls, mediation attempts, humanitarian roles, and internal unity. COVID‑19 produced high collective action, leader neutrality, state partnership, clear positive‑sum goals, and success. All four ethnic conflicts produced low to very low collective action, loss of leader neutrality, the state as protagonist, zero‑sum goals, and failure. The Gurage case involving co‑religionists on both sides demonstrated that even shared faith cannot overcome endogenous partisan divisions. Foundational weaknesses include government co‑optation of religious leaders into the ruling party, financial dependency, and abandonment of religious doctrines demanding justice. Ethnic identity overrides religious authority in endogenous conflicts. The IRCE’s institutional design assumes neutrality that no longer exists when the state is a belligerent and leaders share ethnic identities with combatants. Institutional resilience is domain‑specific: success in public health does not transfer to peacebuilding. During active civil wars, donors should support local, traditional peace custodians (e.g., Aba Gars) rather than national inter‑religious councils, and prioritise internal ethnic de‑escalation within religious bodies before external mediation.